MOUNTAINS UNITE - Svitlana Dovbenko (Vasyl Stefanyk Precarpathian National University, 2015)
Schools in the Ukrainian Carpathian mountain region work in specific conditions. They have original traditions, a special nature of learning and work. Indeed, because of a remote location mountain village school becomes the center for a cultural and spiritual life. Of course, it is related to a present social and economic situation in the country and a slow progress of society. Therefore, we need to look at mountain school with a broader angle, help it in comprehensive development of an individual and ensure an availability of quality education for children living in mountainous areas. Here we should talk about learning as well as laying the foundations for a life success. The international research project Mountain School. Status. Problems. Prospects for Development. Is established to help solve these problems. Precarpathian National University is an active member of the project.